Rediseño del manual de procesos de adquisiciones del Fondo de Cesantía del Magisterio Ecuatoriano F.C.P.C. - Merizalde Lagua, Joseline Elizabeth (2022)
Administrative or operational processes in organizations are essential for the correct and normal development of activities to achieve the expected results. Many processes, whether in the areas of production, marketing, sales, warehousing, logistics, finance, accounting, human talent, among others, are generally known and accepted by employees. The problem lies in the fact that, in many cases, such processes are either not designed, or are not updated according to the realities and new contexts and scenarios that year after year are presented with challenging aspects for the companies, or simply are not formally described and established in a systematic way. The case that concerns us in this research project is more related to the second scenario, that is, processes that even when they exist, have not been duly updated in line with our technologies, new organizational objectives or new and more efficient methods of doing things. The Fondo de Cesantía del Magisterio Ecuatoriano f.c.p.c. has a procurement manual that for a long time was very useful to guide the procurement processes in each of its stages, especially in the case of an entity that, although it is not for profit, manages funds of the teachers' employees, which requires extreme care in each of the stages of such a delicate process as procurement management. The process that we will describe in the following pages is carried out in a normal manner, however, it is evident to many collaborators who work closely with it, that it requires an urgent update, either because there is actually a large gap in some stages of the process induced by technological aspects, or because things are simply being done correctly within the framework of the law, but in a different way from certain aspects indicated in the manual precisely because of the outdatedness we are talking about. We intend to give the necessary update to a priority document in the procurement management of the Fondo de Cesantía del Magisterio Ecuatoriano f.c.p.c. and to contribute to the improvement or optimization of the procurement process by submitting it to the consideration of the institution's officers for an eventual operative application.